Molecular Characterization of Arbuscular Mycorrhizal Fungi in an Agroforestry System Reveals the Predominance of Funneliformis spp. Associated with Colocasia esculenta and Pterocarpus officinalis Adult Trees and Seedlings - Geoffroy, Alexandre; Sanguin, Hervé; Galiana, Antoine; Bâ, Amadou (Frontiers in Microbiology, 2017)
Pterocarpus officinalis (Jacq.) is a leguminous forestry tree species endemic to Caribbean swamp forests. In Guadeloupe, smallholder farmers traditionally cultivate flooded taro (Colocasia esculenta) cultures under the canopy of P. officinalis stands. The role of arbuscular mycorrhizal (AM) fungi in the sustainability of this traditional agroforestry system has been suggested but the composition and distribution of AM fungi colonizing the leguminous tree and/or taro are poorly characterized. An in-depth characterization of root-associated AM fungal communities from P. officinalis adult trees and seedlings and taro cultures, sampled in two localities of Guadeloupe, was performed by pyrosequencing (GS FLX+) of partial 18S rRNA gene. The AM fungal community was composed of 215 operational taxonomic units (OTUs), belonging to eight fungal families dominated by Glomeraceae, Acaulosporaceae, and Gigasporaceae. Results revealed a low AM fungal community membership between P. officinalis and C. esculenta. However, certain AM fungal community taxa (10% of total community) overlapped between P. officinalis and C. esculenta, notably predominant Funneliformis OTUs. These findings provide new perspectives in deciphering the significance of Funneliformis in nutrient exchange between P. officinalis and C. esculenta by forming a potential mycorrhizal network.